Participant's Perception of Sewing Course toward Course and Training Institute in Mattirowalie Village, Tanete Riaja District, Barru Regency - Nurlina Subair; Syahban Nur; Risma Haris; Hasmawati (International Journal of Qualitative Research, 2021)
This study aims at describing the Participant’s Perception of sewing course toward Course and Training Institute in Mattirowalie Village, Tanete Riaja District, Barru Regency. This type of research used in this study applied a descriptive qualitative research method that aims to see the perceptions of the participants in the sewing course. The information in this study consisted of six people, women, and one man. Data collection uses two techniques, namely, interviews and documentation. The results of the study based on interview data obtained from Participant's Perception of sewing course toward Course and Training Institute (LKP), it can be said that sewing course learning has been going well, starting from the implementation of activities and infrastructure. Although there is still much that needs to be improved regarding the learning itself so that participants are never satisfied and continue to learn how to make clothes that have high selling value and the importance of sewing courses for women who want to have the skills to be self-employed.